From magnum opus to patronage building and back again. Problems and solutions in the restoration of the Small Hall of the concert building 'De Vereeniging' in Nijmegen (Bulletin KNOB, 2002)
Concert halls from the beginning of the last century with such a rich ornamental programme as that of the Small Hall in the 'Vereeniging’ in Nijmegen are unknown elsewhere in the Netherlands. This monument is a real gem, resulting from the fertile co-operation between architect Oscar Leeuw (Roermond 1866-1944 Nijmegen), his brother Henri Leeuw jr. (Roermond 1861-1918 Amsterdam) and the painter and later professor Huib Luns (Paris 1881-1942 Amsterdam). Between 1913 and 1917 'De Vereeniging' was drawn, built and decorated.As regards artistry the concert building is undoubtedly to be considered the magnum opus in the oeuvre of Oscar Leeuw, which chiefly consists of villas and shop premises, a hunting lodge. mansions and a synagogue for people with plenty of money to spend. The special appeal of the meanwhile reborn Small Hall does not in the last place result from the combination of architecture, stuccowork and wall paintings as well as the newly designed lighting.The tempestuous developments which the arts went through in the twentieth century - from the urge for decoration of Jugendstil by way of the total lack of decoration of New Realism to Post-modernism - caused 'De Vereeniging' to become rapidly outdated after its opening in 1915. This is a remarkable parallel with the appreciation expressed for the interior of the Rijksmuseum in Amsterdam relatively soon after its opening.Just in time the fortunate decision was taken in Nijmegen to take the original richness of the interior, which is seamlessly linked up with the exterior, as the starting point for an operation aimed at having the building meet present-day requirements again. Thereby restoration went hand in hand with reconstruction and contemporary new construction. A formerly empty shell recovered its inspiring soul.